The first step in solving the equation 5x - 2 = 3 is to add 2 to both sides of the equation.
How to solve the equation
The equation 5x - 2 = 3 is a linear equation in one variable, x.
To solve for x, isolate the variable term on one side of the equation.
Thus;
The first step is to add 2 to both sides of the equation. By doing this, we aim to move the constant term (-2) to the other side, leaving only the variable term (5x) on the left side of the equation.
5x - 2 + 2 = 3 + 2
Simplifying, we have:
5x = 5
Now, we have 5x = 5.
To solve for x, isolate x by itself. Since 5 is being multiplied by x, we can undo this multiplication by performing the inverse operation, which is division.
Divide both sides of the equation by 5:
(5x)/5 = 5/5
Simplifying, we have:
x = 1
So the solution to the equation 5x - 2 = 3 is x = 1.